Balanced Scorecard for Integrity Zone Development: A Study at Padang Class I Immigration Office - Mulyawan, Budy; Purnomo, Agung Sulistyo; Putra, Medyka Pratama (Puslatbang KDOD Lembaga Administrasi Negara, 2025)
The performance of public services in Indonesian government institutions is under significant scrutiny, particularly in terms of achieving Integrity Zone standards such as Corruption-Free Areas (WBK) and Clean and Serving Bureaucratic Areas (WBBM). The objective of this study is to identify strategic steps for enhancing the Integrity Zone (Zona Integritas, ZI) at the Padang Class I Checkpoint Immigration Office using the Balanced Scorecard (BSC) approach. This study examines strategic initiatives to enhance the Integrity Zone at the Padang Class I Checkpoint Immigration Office using the Balanced Scorecard (BSC) framework. This research employs a qualitative approach, utilizing interviews, observations, and document analysis. The study identifies critical gaps in service delivery, financial management, and workforce training. Key findings underscore the need for digital infrastructure upgrades, reallocating resources for staff development, and cultivating a culture of accountability. The study demonstrates the BSC's relevance in public sector reforms, providing actionable insights for improving service efficiency and institutional transparency. By integrating digital governance into the BSC framework, thisresearch advances BSC theory by reconceptualizing its causal relationships in thecontext of integrity-focused bureaucracies, demonstrating how BSC can resolve'measurement fragmentation' between compliance and service excellence